Northern Light : Landscape, Photography and Evocations of the North. - Goldie, Christopher (Image., 2018)
These essays confirm the continued relevance of 'north' as a site of cultural practice and artistic endeavour. If northern regions are tangible realities, the place of varied topography, light, climate, and biogeography, the location of distinct peoples and culture, typically they have been depicted through the traditions of northern landscape representation and the cultural narratives of an era. These discussions - focusing on Scotland, Northern England, Northern Europe, Siberia, the Arctic and Nordic lands - by photographic practitioners as well as theorists, explore and question this tradition, considering landscape as experience, reinterpreting notions of wilderness, emptiness and the sublime.